The Effects of Environmental Uncertainty, Computer Usage, and Management Accounting Systems on Small Business - Ferdinand A. Gul; William Glen; Alan Ruguang Huang (Journal of Small Business Finance, 1993)
The motivation for this contingency-type study is based on the notion that prior studies on management accounting systems (MAS) has almost entirely focused on large business organizations and neglected consideration of the effects of contextual variables and MAS on organizational effectiveness or performance of small business. Using a sample of small business (SB) managers/owners as subjects, this study therefore examined the moderating effects of perceived environmental uncertainty (PEU) and computer usage on die management accounting system (MAS)/performance relationship. Performance in this study was measured using the compound growth rate of market value of the firm (GMV) and growth rate of fixed assets (GFA). SB was defined as companies with between 10 and 100 employees. Results using multiple regression analyses and partial derivatives of the regression equations showed that PEU moderated the effects of MAS on performance with MAS having a positive effect on performance under high levels of PEU. In addition, the results also showed that levels of computer usage moderated the effects of MAS on performance with MAS also having a positive effect on performance under conditions where there was a high level of computer usage. Under low levels of PEU and computer usage MAS had a negative relationship with performance.
Keywords: M41; L25; 650; Environment; Environmental Uncertainty; Computer Usage; Accounting Systems; Small Business